A taxonomic revision of the genus Angelica (Apiaceae) in Taiwan with a new species A. aliensis - Wang, Jenn-Che; Chen, Hung-Hsin; Hsu, Tsai-Wen; Hung, Kuo-Hsiang; Huang, Chi-Chun (Botanical studies, 2024)
Background Angelica L. sensu lato is a taxonomically complex genus, and many studies have utilized morphological and molecular features to resolve its classification issues. In Taiwan, there are six taxa within Angelica , and their taxonomic treatments have been a subject of controversy. In this study, we conducted a comprehensive analysis incorporating morphological and molecular (cpDNA and nrDNA) characteristics to revise the taxonomic treatments of Angelica in Taiwan. Results As a result of our research, we have revised the classification between A. dahurica var. formosana and A. pubescens and merged two varieties of A. morrisonicola into a single taxon. A new taxon, A. aliensis , has been identified and found to share a close relationship with A. tarokoensis . Based on the morphological and molecular characteristics data, it has been determined that the former three taxa should be grouped into the Eurasian Angelica clade, while the remaining four taxa should belong to the littoral Angelica clade. Furthermore, Angelica species in Taiwan distributed at higher altitudes displayed higher genetic diversity, implying that the central mountain range of Taiwan serves as a significant reservoir of plant biodiversity. Genetic drift, such as bottlenecks, has been identified as a potential factor leading to the fixation or reduction of genetic diversity of populations in most Angelica species. We provide key to taxa, synopsis, phenology, and distribution for each taxon of Taiwan. Conclusions Our comprehensive analysis of morphological and molecular features has shed light on the taxonomic complexities within Angelica in Taiwan, resolving taxonomic issues and providing valuable insights into the phylogenetic relationships of Angelica in Taiwan.